Harvesting Environment Mechanical Energy by Direct Current Triboelectric Nanogenerators - Shan, Chuncai; Li, Kaixian; Cheng, Yuntao; Hu, Chenguo (Nano-Micro Letters, 2023)
As hundreds of millions of distributed devices appear in every corner of our lives for information collection and transmission in big data era, the biggest challenge is the energy supply for these devices and the signal transmission of sensors. Triboelectric nanogenerator (TENG) as a new energy technology meets the increasing demand of today's distributed energy supply due to its ability to convert the ambient mechanical energy into electric energy. Meanwhile, TENG can also be used as a sensing system. Direct current triboelectric nanogenerator (DC-TENG) can directly supply power to electronic devices without additional rectification. It has been one of the most important developments of TENG in recent years. Herein, we review recent progress in the novel structure designs, working mechanism and corresponding method to improve the output performance for DC-TENGs from the aspect of mechanical rectifier, tribovoltaic effect, phase control, mechanical delay switch and air-discharge. The basic theory of each mode, key merits and potential development are discussed in detail. At last, we provide a guideline for future challenges of DC-TENGs, and a strategy for improving the output performance for commercial applications. Highlights: 1 The basic theory, key merits and potential development of direct current triboelectric nanogenerator (DC-TENG) from the aspect of mechanical rectifier, tribovoltaic effect, phase control, mechanical delay switch and air-discharge are discussed in detail. 2 This review provides a guideline for future challenges of DC-TENGs, and a strategy for improving the output performance for commercial applications.